Androgen deprivation therapy with Leuprolide acetate for treatment of advanced prostate cancer. (2nd January 2017) - Hoda, M. Raschid; Kramer, Mario W.; Merseburger, Axel S.; Cronauer, Marcus V.
ABSTRACT: Introduction : Hormone sensitive advanced prostate cancer (PCa) is an incurable disease that is treated with a variety of hormonal therapies targeting the androgen/androgen receptor signaling axis. For decades androgen deprivation therapy (ADT) by surgical or chemical castration is the gold standard for the treatment of advanced PCa. Areas covered : This review discusses the pharmacological features of Leuprolide, a luteinizing hormone-releasing hormone (LHRH) agonists/analog and the most commonly used drug in ADT. Expert opinion : Although Leuprolide has been on the market for more than 30 years it is still the leading option for ADT and serves as a basis for most multimodal therapy concepts. The fact that with the onset of castration-resistance in late stage metastatic disease, a prolongation of ADT in combination with a second line hormonal manipulation is recommended supports the importance of the compound for daily clinical practice.